Geotourism And Cultural Prospects of Rupat Island, Bengkalis, Riau - Abdul Aziz; Muhammad Irfan Fadilah; Husnul Kausarian; Hayyan Sabil (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
The area of interest is located on Rupat Island, in the north of the Central Sumatra Basin, and faces directly the Malacca Strait, specifically in the North Rupat District, Bengkalis Regency, Riau Province, with the development of natural tourism objects and attractions. The geology of this area consists of two main formations, namely the Old Superficial Sedimentation Formation (QP) consisting of silt, clay, gravel, and plant residues, and the formation of young sedimentation (QH) consists of clay, silt, slippery gravel, residual plants, and peat swamps. There is also silica sand that is only found on the coastline in the north of Rupat Island, which is greatly influenced by the current of the Malacca Strait as a sediment transportation agent from Indian Ocean and South China Sea. There is a fault structure along with the silica sand deposition creating the main objects of geotourism that are found in the northern Rupat area in the form of Lapin Beach, Pesona Beach, Tanjung Api Beach, and Beting Aceh Beach. To visit the geotourism area both road and sea by boat, also made supporting facilities such as homestays, local road points, and signboard. There is also a diversity of flora and fauna in the form of pine trees, and mangrove forests, mammals such as deer, birds such as hombills, crows, and primates such as long-tailed monkeys, beruk and lutung are quite easy to find along the mangrove forest. There is a diversity of Malay cultures such as Zapin Dance and Safar Bathing. This research was aiming to develop geotourism prospects that have not been explored and create new potential for tourism products in North Rupat, Rupat Island.